Development Media Interactive Learning to Build Concept Training Guild Two Tangent Circles - Vivin Nur Afidah (Universitas Negeri Malang, 2014)
Pengembangan Media Pembelajaran Interaktif untuk Membangun Pemahaman Konsep Garis Singgung Persekutuan Dua Lingkaran Abstract: Media developed interactive learning is interactive learning media that is designed based on the characteristics of learning with the help of computer / Computer Assisted Instruction (CAI) type tutorial. Designed by cognitive load theory that minimizes processing extraneous cognitive load, adjust the intrinsic cognitive load processing, and developing processing germane cognitive load. The research follows the development of 4D development model that define (defining), design (design), develop (development), and disseminate (dissemination). The conclusion is (1) the results of the validation by experts and practitioners assess media interactive learning developed valid, (2) the results of teacher and student activity observation showed media interactive learning meet the criteria of practicality, (3) the results of the quiz show most students attain a minimum level of understanding high , (4) the results of tests mastery of teaching materials showed most students achieve minimum mastery level is high, (5) the results of quizzes and tests mastery of teaching materials and student questionnaire responses showed interactive learning media has met the criteria effectively. specified that the understanding and mastery of the material communion of two circles tangent meet the minimum categories of high and students' response to the use of interactive learning media showed a positive response. Key Words: development, interactive learning media, tangents, circle Abstrak: Media pembelajaran interaktif yang dikembangkan adalah media pembelajaran interaktif yang dirancang berdasarkan karakteristik pembelajaran dengan bantuan komputer/Computer Assisted Instruction (CAI) tipe tutorial. Dirancang berdasarkan teori beban kognitif yaitu meminimalkan pemrosesan beban kognitif  extraneous, mengatur pemrosesan beban kognitif intrinsic, dan mengembangkan pemrosesan beban kognitif germane. Penelitian pengembangan mengikuti model pengembangan 4D yaitu define (pendefinisian), design (perancangan), develop (pengembangan), dan disseminate (pe-nyebarluasan). Simpulannya adalah (1) hasil validasi oleh ahli dan praktisi menilai media pembelajaran interaktif yang dikembangkan valid, (2) hasil pengamatan aktivitas guru dan siswa menunjukkan media pembelajaran interaktif memenuhi kriteria kepraktisan, (3) hasil kuis menunjukkan sebagian besar siswa mencapai tingkat pemahaman minimal tinggi, (4) hasil tes penguasaan bahan ajar menunjukkan sebagian besar siswa mencapai tingkat penguasaan minimal tinggi, (5) hasil kuis dan tes penguasaan bahan ajar serta angket respon siswa menunjukkan media pembelajaran interaktif telah memenuhi kriteria efektif. yang ditetapkan yaitu pemahaman dan penguasaan materi garis singgung persekutuan dua lingkaran memenuhi kategori minimal tinggi serta respon siswa terhadap penggunaan media pembelajaran interaktif menunjukkan respon positif. Kata kunci: pengembangan, media pembelajaran interaktif, garis singgung, lingkaran